Lytic Phages against ST11 K47 Carbapenem-Resistant Klebsiella pneumoniae and the Corresponding Phage Resistance Mechanisms - Qingqing Fang; Zhiyong Zong (mSphere, 2022)
ABSTRACT We isolated and characterized a novel phage from hospital sewage, P13, able to lyse ST11 K47 carbapenem-resistant Klebsiella pneumoniae (CRKP), a major CRKP lineage. P13 formed a large lytic plaque (3.0 to 6.0 mm in diameter) in double-layer LB agar after overnight coculture with its host bacterial strain. A translucent halo formed when the culture was prolonged to 48 h. P13 showed a narrow host range only lysing ST11 K47 CRKP with a burst size of around 167 PFU/cell and exhibited broad pH and thermal stability. Genome sequencing showed that P13 contains no virulence, lysogenic or antimicrobial resistance genes, making this lytic phage a potential agent for phage therapy. Transmission electron microscopy showed that P13 exhibited typical morphology of the family Podoviridae with an isometric head and a short noncontracted tail. Genomic analysis showed that P13 belongs to a novel species of the genus Przondovirus, subfamily Studiervirinae, family Autographiviridae. P13-resistant mutants of bacteria emerged after 4 h exposure to the phage. Interruptions of wbaP (encoding capsule polysaccharide synthesis) by insertion sequence IS903B mediated P13 resistance. The rapid emergence of resistant mutants represents a disadvantage for P13 as a therapeutic phage and highlights the need for recovery of a range of phages binding to different surface receptors of host bacteria to further extend their utility as a potential tool against CRKP. IMPORTANCE Carbapenem-resistant Klebsiella pneumoniae (CRKP) is a major challenge for infection control and clinical management. Alternative therapies to antimicrobial agents are urgently needed and bacteriophages (phages) are an attractive option. However, more novel lytic phages and more studies to reveal phage-resistant mechanisms are needed to overcome phage resistance. In this study, we isolated and characterized a novel species of lytic phage active against CRKP. We found this phage exhibited delayed formation of halo, which is atypical compared to other characterized similar phages, and we provide an explanation for this phenotype based on genomic analysis. We also identified mechanisms mediating resistance to the phage.